Small mammal activities structure fine-scale soil microbial communities and coordinate rodenticide effects in the typical steppes of China - Wei Liu; Tingbei Bo; Ning Zhao; Bin Hu; Gaojian Li; Zhishu Xiao (Ecotoxicology and Environmental Safety)
Soil microbial community is a diverse combination of microbial species that is influenced by soil moisture, physicochemical properties, biological activities, and other factors. Brandt's vole (Lasiopodomys brandtii) is a small rodent distributed in the typical steppes of China, Mongolia, and Russia, which often causes serious pest to the local areas when its population outbreaks. Yet the impacts of rodenticides on soil microbial diversity and ecosystem functions in Brandt’s vole habitats are not well-known. In this study, we compared the microbial community composition and functional genes between the central and peripheral areas of undisturbed cave communities, as well as grasslands with and without rodenticides. The results showed that the activity of field voles and rodenticides had a significant impact on soil microbial communities, antibiotic resistance genes, and soil element cycling. The use of rodenticides reduces the activity of rodents, reduces pathogenic bacteria in the soil. The use of rodenticides inhibits N cycling, while rodent activity promotes the N cycling. Relative abundance of dissimilatory nitrate reduction nitrate (narGHI or napA), denitrification nitrous oxide (nosZ), nitrogen fixation nitrogen (nifH), denitrification nitric oxide (norB) were significantly decreased in rodenticide soil. The activity of rodents increases the abundance of specific antibiotic resistance genes (ARGs), while rodenticides reduce the abundance of AGRs in the soil. Our study for the first time explores the interaction effects of rodent activity and rodenticide use on soil, providing a reference for understanding the multifunctionality of soil ecosystems and the response of microbial communities to external disturbances (rodents and humans) in the future.